The Measurement of Organizational Efficiency in Chosen Food Processing Enterprises in Poland - Anna ZIELINSKA-CHMIELEWSKA (Communications of International Proceedings, 2020)
The issue of efficiency of food processing enterprises is ever-present because of the continuous process of improving the quality standards of raw materials, complying with the procedures in food production, introduction of modern production technology and, above all, due to the large number of actors who are competing for customers in the domestic and foreign food market. In the coming years Polish food processing sector will be facing significant challenges with the inevitable slow and gradual decrease in the cost advantages of raw materials’ prices, as well as ready to eat products. Enterprises, as they constitute the majority in manufacturing business, in the long run will need to determine the efficiency, and hence competitiveness of Polish food processing sector. The aim of the paper is to review the domestic and foreign literature in terms of classification and systematization of the concept of organizational efficiency in chosen food processing enterprises in Poland. In the theoretical part of the study methods of descriptive, comparative, deductive and synthetic analysis are used. In the practical part of the study appropriately selected qualitative methods such as questionnaire is presented. The results of the analysis is based on the results of authors’ own calculations, as well specific findings from business practice both from inland and abroad.
Keywords: Effectivity; Efficiency; Organizational Efficiency; Food Processing Sector.